Increasing Teacher Competence in Compiling Level Higher Order of Thinking Skill (HOTS) Questions through the Empowerment of Subject Teacher Consultations: Peningkatan Kompetensi Guru dalam Penyusunan Soal Level Higher Order of Thinking Skill (HOTS) Melalui Pemberdayaan Musyawarah Guru Mata Pelajaran (MGMP) - Umi Mazro’ah (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2023)
Teacher competence is the overall knowledge, skills, and values attached to the teacher, which are reflected in his teaching assignments. Higher Order of Thinking Skills (HOTS) are high-level thinking skills in cognitive hierarchies such as analysis (C4), evaluation (C5), and creation (C6). The purpose of this school action research was to find out the process and competency improvement of SMPN I Bringin teachers in compiling questions at the Higher Order of Thinking Skills (HOTS) level through school-level MGMP empowerment. Through empowering the MGMP at the school level, there has been an increase in the competence of teachers at SMPN I Bringin Kab. Semarang in the preparation of HOTS level questions, namely the average teacher competence in the first cycle was 76% and the pre-cycle average was 22.5%, so that there was an increase in the average of 53.5%. In cycle II, the average teacher competency reached 100%, and in cycle I, the average was 76%, resulting in an average increase of 24%. With a target indicator of teacher competency success of 90%, teacher competency in cycle I (76%) has not met the target, but in cycle II (100%), teacher competency has exceeded the target. Abstrak Kompetensi guru adalah keseluruhan pengetahuan, keterampilan, dan nilai-nilai yang melekat pada guru yang direfleksikan dalam tugas keguruannya. Higher Order of Thinking Skilss (HOTS) merupakan keterampilan berpikir tingkat tinggi dalam hirarki kognitif seperti analisis (C4), evaluasi (C5), dan kreasi (C6). Tujuan penelitian tindakan sekolah ini adalah untuk mengetahui proses dan peningkatan kompetensi guru SMPN I Bringin dalam penyusunan soal level Higher Order of Thinking Skills (HOTS) melalui pemberdayaan MGMP tingkat sekolah. Melalui pemberdayaan MGMP tingkat sekolah telah terjadi peningkatan kompetensi guru SMPN I Bringin Kab. Semarang dalam penyusunan soal level HOTS yaitu rerata kompetensi guru pada siklus I sebesar 76% dan rerata pada pra siklus sebesar 22,5% sehingga terjadi kenaikan rerata sebesar 53,5%. Pada siklus II rerata kompetensi guru mencapai 100%, dan pada siklus I reratanya adalah 76%, sehingga terjadi kenaikan rerata sebesar 24%. Dengan target indikator keberhasilan kompetensi guru sebesar 90%, kompetensi guru pada siklus I (76%) belum memenuhi target, namun pada siklus II (100%) kompetensi guru telah melampaui target.